Analisis Kesiapan Perubahan Individu Dalam Penerapan Sistem Perbendaharaan Dan Anggaran Negara (SPAN) Lingkup Kanwil Ditjen Perbendaharaan Provinsi Sulawesi Utara - setianto, Andi (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
Individual readiness to changes to overcome resistance plays an important role in the implementation of a change. The purpose of this study was to determine the readiness of individual changes, differences in readiness changes based on the profile of respondents, and examine the effect of predictors of readiness of individual changes in the state treasury and budget system. Compare means test research results show that The results of different test shows that there is no difference in readiness for changes in gender, age, work period and level of education. The regression analysis showed positive influence of independent variables on the dependent variable.Keywords: Indovidual readiness to change, organizational commitment, perceived organizational support, employee engagement